2009
DOI: 10.1111/j.1553-2712.2009.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Single and Combined Diagnostic Value of Clinical Features and Laboratory Tests in Acute Appendicitis

Abstract: Objectives: The objective was to evaluate the diagnostic accuracy of clinical features and laboratory test results in detecting acute appendicitis.Methods: Clinical features and laboratory test results were prospectively recorded in a consecutive series of 1,101 patients presenting with abdominal pain at the emergency department (ED) in six hospitals. Likelihood ratios (LRs) and the areas under the receiver operating characteristic curve (AUC) were calculated for the individual features. Variants of clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 19 publications
(32 reference statements)
4
26
0
Order By: Relevance
“…Our NAR is comparable to other studies [14][15][16][17]. Various authors have reported that the highest incidence of NAR occurs in females of the reproductive age group (15-49 years) [5,6,13,18]. Although we also recorded a higher incidence in this population, the highest incidence was found in young girls aged 11-20 years.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our NAR is comparable to other studies [14][15][16][17]. Various authors have reported that the highest incidence of NAR occurs in females of the reproductive age group (15-49 years) [5,6,13,18]. Although we also recorded a higher incidence in this population, the highest incidence was found in young girls aged 11-20 years.…”
Section: Discussionsupporting
confidence: 73%
“…These authors suggest that CRP is inexpensive, reduces NAR, and thereby decreases financial burden on the governmental health-care setup [9,20]. The combination of TLC and CRP, however, correlates better than any one of these investigations alone [9,12,13,20]. CRP was not performed in our patients as this facility is not present in our emergency department.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Combinations of clinical features-including pain migration, abdominal rigidity, and elevated inflammatory parameters-have a high predictive value for appendicitis, 7,8 but they are present in only a small proportion of patients suspected of having appendicitis. 9 This makes the clinical diagnosis of appendicitis difficult in the majority of cases and emphasizes the need for imaging in patients suspected of having appendicitis. Several studies have shown that the routine use of imaging has a positive effect on patient outcomes, with two randomized controlled trials reporting substantially lower negative appendectomy rates with routine imaging in all patients, compared to selective use of imaging based on clinical judgment.…”
Section: Resultsmentioning
confidence: 99%
“…12,19 Development of the CDR. Fourteen clinical variables known to be associated with acute appendicitis based on previous studies 9,21 were evaluated in the development set in patients with inconclusive or negative US. For each variable we estimated the diagnostic odds ratio (OR) for a final diagnosis of acute appendicitis, with corresponding 95% confidence interval (CI), using univariable logistic regression analysis.…”
Section: Study Protocolmentioning
confidence: 99%